Studying beef production evolution to plan for ecological intensification of grazing ecosystems. (February 2023) - Caram, Nicolas; Soca, Pablo; Sollenberger, Lynn E.; Baethgen, Walter; Wallau, Marcelo O.; Mailhos, María E.
Abstract: CONTEXT: A challenge facing the livestock sector is improving beef production while mitigating negative environmental impacts. Analyzing its past productive and environmental performance may elucidate strategies for improving efficiency of grassland-based systems and identify future research and public policy priorities. OBJECTIVES: Describe past and current dynamics and assess potential future scenarios of the Uruguayan beef production sector, considering historical beef production growth rate (kg carcass), partitioning in land use by the cattle sector (ha), cattle animal performance (kg carcass animal −1  year −1 ) and stocking rate (animal ha −1 ) since 1966. METHODS: We quantified drivers of beef production and total enteric methane (CH4 ) emissions and modeled the gap between their current and potential levels by applying new management practices at country scale. Potential systems included reduced age of replacement heifers at first pregnancy and greater cow weaning rates. Results AND CONCLUSIONS: Cattle land area expansion and increased animal performance explained most of beef production growth (33 and 52%, respectively), while stocking rate had a negligible effect. We identified that recent beef production was driven by improved pasture area (R 2  = 0.42), which represented only 21% of cattle area. This disproportionate effect showed a dependency of national beef production on improved pastures. The current weaning rate (65%) and the number of replacement heifers that have first pregnancy by 36 months of age (480, 000 heads) revealed a national inefficiency, falling short of the potential of grazing systems based on native pastures. When concepts and principles of ecological intensification of native pasture grazing systems are applied optimally, weaning rate can be increased from 65 to 85% and age of first pregnancy reduced from 36 to 24 months, decreasing national enteric CH4 emissions by 13%. The weaknesses identified in the national beef production sector support re-focusing research, public policy, and technologies applied by farmers to shift the paradigm of beef production to greater ecological intensification based on native pastures. In this way, it will be possible to increase beef production and mitigate environmental impacts of grazing systems. SIGNIFICANCE: We demonstrate that re-focusing beef production from improved pastures to native pastures, while enhancing their management, will mitigate the CH4 emissions of the beef sector at large scales and will underpin the annual beef production, leading to a stable annual production, reducing the dependency on improved pasture area and providing ecosystem services. Graphical abstract: Unlabelled Image Highlights: Studying past productive and environmental performance identifies strategies to improve future beef production. National beef production has been highly dependent on improved pastures. Shifting productive paradigm to native pastures may stabilize beef production, reducing Uruguay enteric CH4 emissions by 13%. Refocus research, public policy and technologies to native pastures allow the ecological intensification of grazing systems.